Profesionalisme Dakwah Ustadz dan Ustadzah TPQ Miftahul Ulum dalam Merespons Sikap Interpretasi Kritis Masyarakat - Hariansyah, Novan (Maddah: Journal of Advanced Da'wah Management Research, 2024)
Dakwah professionalism is crucial amidst the global flow of information that critically examines religious teachings. Challenges arise from the increasing access of society to critical perspectives through social media, which can lead to the misinterpretation of Islam. With 60% of the population increasingly relying on online information sources, the potential for misinterpretation of Islam has significantly increased. As educators and moral guides, ustadz and ustadzah are not only responsible for teaching the Qur’an but also for shaping the character of their students to be strong both spiritually and morally. The aim of this research is to examine the professionalism of dakwah ustadz and ustadzah at TPQ Miftahul Ulum in responding to society's critical interpretive attitudes. The methodology used in this study is qualitative research. Dakwah professionalism at TPQ Miftahul Ulum is reflected through five main aspects: 1) the implementation of innovative methods that link religious lessons with daily life, 2) the utilization of technology, such as educational videos, to enhance the attractiveness of learning, 3) structured memorization that reinforces the understanding of the meaning of the verses, 4) formative and summative assessments that monitor the development of the students, and 5) reflection sessions and group discussions that support continuous understanding and improvement.